2017
DOI: 10.13005/msri/140211
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of ZnO Nano Particles, its Characterization and Application

Abstract: Nano ZnO was synthesised by green approach employing aqueous extract of Adulsa and Lemongrass leaves. XRD suggested hexagonal wutzite structure for these prepared ZnO. Synthesised nanoparticles efficiently catalysed Biginelli reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
3
4
0
Order By: Relevance
“…The SEM magnification images indicated that the ZnO NPs are spherical, hexagonal shaped NPs with irregular morphology and aggregated NPs. Our study results are comparable with the earlier reports [ 38 ]. Biosynthesized ZnO NPs SEM images in different magnifications are shown in Fig.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The SEM magnification images indicated that the ZnO NPs are spherical, hexagonal shaped NPs with irregular morphology and aggregated NPs. Our study results are comparable with the earlier reports [ 38 ]. Biosynthesized ZnO NPs SEM images in different magnifications are shown in Fig.…”
Section: Resultssupporting
confidence: 93%
“…ZnO NPs morphology was assessed by using SEM (VEGA 3 TESCAN). The synthesized ZnO NPs was prepared as thin film by placing a small volume of synthesized ZnO NPs on the carbon coated copper grid, blotting paper was used to remove the extra solution and the thin film was dried [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoparticles synthesized in the present study are predominantly spherical and crystalline in shape. Other studies have also reported the same shapes especially spherical, for fabricated zinc oxide nanoparticles (Anvekar, Chari, & Kadam, 2017;Hoseinpour et al, 2017;Jamdagni, Khatri, & Rana, 2018). Furthermore, XRD spectrum showed that the zinc oxide nanoparticles have hexagonal structures and their average diameter is 35.88 nm.…”
Section: Discussionmentioning
confidence: 57%
“…There are two types of nanoparticles namely metal and metal oxide nanoparticle them are very important but metal oxide nanoparticle such as CuO, TiO 2 and ZnO have semi properties. Now-a-days ZnO nanoparticle has great attention among researchers owing to its different characteristics such as conductivity and cytotoxicity [3 synthesis of ZnO nanoparticles from leaves such as Moringa oleifera, Lemon grass, C and Catharanthus roseus has already been reported [4][5][6][7][8]. In our point of view, ZnO nanoparticles from Jasminum Fluminense using Zinc acetate and Sodium hydroxide as starting material first time.…”
Section: Nanopowder Jasminummentioning
confidence: 99%